2021
DOI: 10.1055/a-1390-4061
|View full text |Cite
|
Sign up to set email alerts
|

Psychoonkologische Versorgung von Menschen mit Migrationshintergrund und ihren Angehörigen – Ergebnisse aus leitfadengestützten Einzelinterviews mit Ärztinnen und Ärzten

Abstract: Zusammenfassung Hintergrund Menschen mit Migrationshintergrund stellen eine heterogene Bevölkerungsgruppe dar mit einer Vielfalt an Ethnien, kulturellen und religiösen Ansichten und Erfahrungen. Die Diagnose und anschließende Behandlung einer Krebserkrankung gehen mit vielfältigen psychosozialen Belastungen einher. Daher war es Ziel dieser Studie, die aktuelle Perspektive von Ärzt/i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 23 publications
1
11
0
4
Order By: Relevance
“…Hence, these results are difficult to compare to previous studies on the topic, which took place in healthcare systems different from the one in Germany and focused on ethnic groups rather than on migration background [ 1 , 3 ]. Following Hempler et al [ 28 ], a higher chance of experiencing financial difficulties for cancer survivors with a migration background might be due to the lack of knowledge of the German health system. The study reported the perception of medical personnel according to whom this lack of knowledge led to untimely planning of financial support or insurance coverages [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, these results are difficult to compare to previous studies on the topic, which took place in healthcare systems different from the one in Germany and focused on ethnic groups rather than on migration background [ 1 , 3 ]. Following Hempler et al [ 28 ], a higher chance of experiencing financial difficulties for cancer survivors with a migration background might be due to the lack of knowledge of the German health system. The study reported the perception of medical personnel according to whom this lack of knowledge led to untimely planning of financial support or insurance coverages [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, speculations have been published on a possible association between migration background and financial difficulties. In a series of qualitative interviews, Hempler et al [ 28 ] reported that oncological personnel in Germany considered patients with cancer and migration background to have higher risk to experience financial difficulties due to lower health literacy and reduced ability to navigate the German health system.…”
Section: Introductionmentioning
confidence: 99%
“…Thematik ein sinnvoller Ansatz zur Gewinnung von Teilnehmenden sein. Aufgrund von Hinweisen aus der Literatur [5] und Hinweisen aus den qualitativen Interviews mit Ärztinnen und Ärzten [3] , haben wir in unserer Studie jedoch davon abgesehen. Sowohl eine Krebserkrankung als auch psychische Gesundheitsprobleme können in einigen kulturellen bzw.…”
Section: Diskussion Und Zukünftige Lösungsstrategien („Lessons Learned“)unclassified
“…Studien deuten darauf hin, dass der Bedarf und die Inanspruchnahme der psychoonkologischen Versorgung von Krebserkrankten sich bei Menschen mit Migrationshintergrund aus dem europäischen Ausland weniger stark von denjenigen ohne Migrationshintergrund unterscheiden als bei Menschen aus dem außereuropäischen Ausland. Insbesondere Menschen aus dem Nahen und Mittleren Osten wurden in bisherigen Studien zum psychoonkologischen Versorgungsbedarf kaum berücksichtigt, weswegen in unserer Studie der Fokus auf diese Herkunftsgruppe gelegt wird [3] , [4] . Zu diesem Zweck haben wir speziell Betroffene aus dem Mittleren und Nahen Osten unter anderem mithilfe von leitfadengestützten qualitativen Einzelinterviews befragt.…”
Section: Introductionunclassified
See 1 more Smart Citation